ANALISIS SPATIAL KONDISI TUTUPAN LAHAN ANTAR WAKTU PADA KAWASAN HUTAN MANGROVE MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) DI TWA MANIPO DESA ENORAEN KECAMATAN AMARASI TIMUR KABUPATEN KUPANG - Manyus Mariyanto; Ludji Michael Riwu Kaho; Norman P.L.B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
Manipo Nature Park is one of nature conservation areas and government administratively included in the area of Enoraen Village, East Amarasi District, Kupang Regency. This study is aimed to 1) to determine the condition of land cover and multy temporal in 1992, 2005 and 2018 in the Mangrove Forest Area in Manipo Nature Park , 2) Utiliization and how to operate GIS to analyze land coverchanges in Mangrove forest area in Manipo Nature Park. This research was conducted in February – April 2019 using the method of Object Based Image Segmentation ( OBIS) and Normalize Difference Vegetation Index (NDVI). In the result of the analysis using the OBIS method, it was found that the image analysis in 1992, 2005, and 2018 revealed that the area of land cover rose and fell changes in the condition of Mangrovevegetation can also be referred to as succession and then to determine the level of density using NDVI method 2018, namely the total area of Mangrove cover with dense land cover class is only 0,02% of the total land area of 399 Ha and the area of cover Mangrove lands with the class of land cover rarely increase with a total area of 332.07 or 83,31 % of the total Mangrove area in 2018